Analisis Forecasting Produksi Benih Kentang (Solanum tuberosum L.) di UPT. Benih Induk Hortikultura Kutagadung-Berastagi - Rahmika, Sibagariang; Rozalina; Kiagus M. Zain , Basriwijaya (Jurnal Penelitian Agrisamudra, 2024)
This study aims to analyze the forecasting of potato seed production at UPT. Horticultural Parent Seed Kutagadung-Berastagi in 2024-2033 whether it will increase or not. The method of determining the area is done by purposive technique (intentionally). The object in this study is the data of UPT. BIH Kutagadung-Berastagi in 2014-2023. The data analysis methods used are the trend method and classical assumption test, simple linear regression analysis and hypothesis testing. The results of the trend method test show that the most appropriate method in predicting potato seed production is a linear trend with the smallest MSE value of 1,128,008.215 and the smallest MAPE value of 4%. and shows that the time variable (X) has an effect on increasing potato seed production (Y) at UPT. BIH Kutagadung-Berastagi with a significant value of 0.016. The results of the forecasting analysis in this study indicate that potato seed production at UPT. BIH Kutagadung-Berastagi in 2024-2033 experienced a positive/increasing trend.